Influência da luz da lua sobre à agregação de machos de Nyssomya whitmani, vetor da leishmaniose cutânea americana no Brasil - BRITO, Gildene da Silva (2020)
The species Nyssomya whitmani (Antunes & Coutinho) is a vector of cutaneous leishmaniasis. Males of this species exhibit the behavior of forming mating aggregations under or near hosts. In the literature, there is little information about this, not to mention the influence of moonlight on this behavior. In this sense, to verify the influence of moonlight on the aggregation activity of males, experimental cages were used, with chickens and suction traps without light. In total, 2160 individuals of sandflies were captured, distributed in 7 species, during the 18 nights of collection in the presence and absence of moonlight. The most abundant species was N. whitmani, males of this species were more abundant in the presence of the moon (92. 67 ± 17.17 / mean ± SE) compared to the nights without moon (37 ± 8,168 / mean ± SE) and this difference was statistically significant (P = 0.0044). The male: female ratio on moonless nights was 1: 1, and on moonlit nights it was 1.7: 1. In view of the results, it is observed that the moonlight did in fact influence the aggregation activity of the males, due to the increase in the number of sandflies in the hosts.